PENGARUH PELATIHAN FISIK, MENTAL TERHADAP KINERJA PETUGAS PEMASYARAKATAN DI LINGKUNGAN LAPAS KELAS IIA SERANG: PENGARUH PELATIHAN FISIK, MENTAL, DAN DISIPLIN TERHADAP KINERJA PETUGAS PEMASYARAKATAN DI LINGKUNGAN LAPAS KELAS IIA SERANG - setianingsih, sulis; Munawaroh, Munawaroh; Prasongko, Prihambodo Dwi; Susanti, Tri Meliani (Jurnal Manajemen dan Bisnis, 2025)
This research aims to analyze the influence of physical training, mental training, and discipline on the performance of correctional officers at Class IIA Serang Prison. The performance of officers is a crucial element in the successful implementation of correctional tasks, which include security, coaching, and the social reintegration of inmates. This study uses a quantitative approach with multiple linear regression analysis techniques on secondary data. The results of this study indicate that physical training, mental training, and work discipline have a positive and significant impact on the performance of community service officers in the class IIA Serang prison environment. The results of this research are expected to contribute to the development of human resource policies in the correctional environment.